Phenotypic methods for determination of methicillin resistance in Staphylococcus spp. from health care workers - Marcelle Aquino Rabelo; Armando Monteiro Bezerra Neto; Eduardo Caetano Brandão Ferreira da Silva; Wagner Luis Mendes de Oliveira; Fábio Lopes de Melo; Ana Catarina S. Lopes; Nilma Cintra Leal; Maria Amélia Vieira Maciel (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Staphylococcus spp. is an important healthcare-associated pathogen and the identification of methicillin-resistant strains in samples of colonization may provide data to assist in the antimicrobial therapy success. OBJECTIVES: To determine the occurrence of colonization by methicillin-resistant Staphylococcus spp. (MRS), through the detection of the mecA gene and to evaluate different phenotypic methods for the presumptive detection of methicillin resistance in samples of the anterior nasal cavity and hands of the health care personnel of a university hospital in the state of Pernambuco, Brazil. METHODS: We selected the 28 isolates of Staphylococcus spp., which showed an intermediate or resistant phenotypic profile for oxacillin, detected by the Kirby Bauer technique. The methods used were disk-diffusion tests for cefoxitin, minimal inhibitory concentration by E-test for oxacillin, screening for oxacillin resistance and mecA gene detection by polymerase chain reaction (PCR). RESULTS: About the phenotypic methods utilized, only the E-test of oxacillin did not show a statistically significant difference in relation to PCR for the mecA gene detection, considered the gold standard. CONCLUSION: The E-test of oxacillin was the best of the phenotypic methods utilized. It is necessary to correctly detect MRS in healthy individuals, because they can act as carriers and can therefore be a potential source of microorganisms involved in hospital infections.